FPGA based re-configurable wireless sensor network protocol - Chalivendra, Gayathri; Srinivasan, Renuka; Murthy, Nukala Satyanarayana (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/